Perceived Effect of Climate Change on Library Resources in Universities in Edo State, Nigeria - Aba, Jane Igie; Makinde, Osasu Theresa; Omigie, Christopher Agbeniaru; Ademola, Adeniran (Communicate: Journal of Library and Information Science, 2023)
Climate change is a menace to the universe, resulting from both human activity and uncontrollable natural factors. The effects of climate change are harmful and have a severe impact on library resources. The primary objective of this study is to examine the perceived effects of climate change on library resources in universities in Edo State, Nigeria. Data was collected using a descriptive survey design. The population was 115 library staff from three (3) University libraries in Edo State. Data collected were analyzed using frequency counts, percentages (%), mean ( ) and Standard Deviation (SD). Result reveals that perceived effects of climate change on library resources include temperature, relative humidity, pests, pollutants, and light, which damage library structures and furnishings, decrease library usage during rainy season, and raise users frustration in university libraries in Edo State, Nigeria. Climate change-related variables are threats that have a direct or indirect impact on library resources. It is expected that librarians should receive ongoing training on the physical and chemical nature of resources, and significant efforts by library administration, employees, and parent institutions are required to address the threat of climate change on library resources in universities in Edo State, Nigeria.